Efeito de nanotubos de carbono de parede múltipla em girinos de Lithobates catesbeianus (SHAW, 1802) sobre biomarcadores em diferentes níveis de organização biológica - de Souza, Bruno Fernando Santos (2019)
The search for materials improvement brought the development of nanoparticles, which environmental and health consequences from its use are slightly understood. Added to that context the drastic populational decline of amphibians represents a concern due to their increased susceptibility to pollutants. Thus, the present study aimed to investigate toxical potential of multi-walled carbon nanotubes (MWCNT) at concentrations of 0.1 and 10 mg.L-1 associated with surfactant Pluronic™ F-127 (0,1%) and the isolated surfactant in North American bullfrog tadpole (Lithobates catesbeianus, SHAW, 1802) via biomarkers on different levels of biological organization. The animals (n = 12 per group) were individually exposed (96 hours), the results were compared to the control group. The animals were photographed, measured, heart rate and venipunctured for blood sample (total erythrocytes, differential leukocytes, nuclear abnormalities and comet assay). A decrease in body mass, with no change in body size, activity level and stage of development were observed, which indicates energy deviation to detoxification processes of the xenobiotics. There was also tachycardia in the 0.1% Pluronic ™ F-127 and 10 mg.L-1 MWCNT + Pluronic ™ groups, with no change in the lowest concentration of the nanoparticle, indicating increased cardiac performance related to homeostatic response to increase perfusion and oxygenation of tissues responsible for detoxification, corroborated by increased erythrocytes in the 0.1% Pluronic ™ F-127 group. The immunological response to the xenobiotics indicated hypersensitivity (allergenic response) to MWCNTs and neutropenia, possibly caused by Pluronic ™ F-127 surfactant in all groups, representing increased susceptibility to fungi. Genetic damage occurred to all xenobiotics, however the damages were conserved only in the highest concentration of MWCNTs. Moreover the body pigmentation of the animals exposed to MWCNTs was reduced, probably due to the increase of melatonin secretion and decreased stimulation of melanopsin. In addition, the association between Pluronic ™ F-127 and MWCNTs often resulted in responses different from those when surfactant was used alone, probably due to competition from the surfactant / nanoparticles / biological system interaction, indicating the relevance of the study of the dispersing compounds of the materials of interest, as well as the biomarkers in different levels of biological organization. In general, the results point to the urgency of new strategies and public policies aimed at the environmental preservation, especially to the anuran amphibians.